Floods in relation to reservoir practice reprint of the Interim report of the Committee on Floods 1933, with additional data on floods recorded in the British Isles between 1932 and 1957. (Institution [of Civil Engineers], 1960)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Reprinted in 1960, with additional data on floods recorded in the British Isles between 1932 and 1957.
Keywords: Flood dams and reservoirs -- Great Britain.; Floods -- Great Britain.; elektronické knihy; electronic books